In-orbit performance of the soft X-ray imaging system aboard Hitomi (ASTRO-H). (11th April 2018) - Nakajima, Hiroshi; Maeda, Yoshitomo; Uchida, Hiroyuki; Tanaka, Takaaki; Tsunemi, Hiroshi; Hayashida, Kiyoshi; Tsuru, Takeshi G; Dotani, Tadayasu; Nagino, Ryo; Inoue, Shota; Ozaki, Masanobu; Tomida, Hiroshi; et al.
Abstract: We describe the in-orbit performance of the soft X-ray imaging system consisting of the Soft X-ray Telescope and the Soft X-ray Imager aboard Hitomi. Verification and calibration of imaging and spectroscopic performance are carried out, making the best use of the limited data of less than three weeks. Basic performance, including a large field of view of 38^′ × 38^′ , is verified with the first-light image of the Perseus cluster of galaxies. Amongst the small number of observed targets, the on-minus-off pulse image for the out-of-time events of the Crab pulsar enables us to measure the half-power diameter of the telescope as ∼1 ^′_. 3 . The average energy resolution measured with the onboard calibration source events at 5.89 keV is 179 ± 3 eV in full width at half maximum. Light leak and crosstalk issues affected the effective exposure time and the effective area, respectively, because all the observations were performed before optimizing an observation schedule and the parameters for the dark-level calculation. Screening the data affected by these two issues, we measure the background level to be 5.6 × 10 −6 counts s −1 arcmin −2 cm −2 in the energy band of 5–12 keV, which is seven times lower than that of the Suzaku XIS-BI.